(3GdJHjGf aj BOGH MedI GdbQBfs - (3jMji Hf TQa Hf eQj Hf MSf GdMRGej GdMhQGfj, Gdfhhj, GdTGaYqj, CHh RcQjG, eMjj GdOjf, (B676 (3g` s ((3YHO Gddg Hf YHO Gddg GdebQi s)
(3ChdgG (B:s
(3GdMeO ddg GdcQje GdefGf Pi GdWhd hGdaVd hGdEMSGf CeG HYO aEf Gddg SHMGfg hJYGdi ef Ydi gPg GdCeI RGOgG Gddg JYGdi TQakG HGdOjf hgPg agQSJ CHhGHg GdHGH GdChd ai CWQGa ef aVjdI JdGhI GdbQBf hMedJg s
(3BNQgG (B:s
(3heG PcQJg ef GdXGgQ abUOJ HjGfg def dG jNGdW GdYdeGA aEfg jfJaY Hg Ef TGA Gddg JYGdi gPG BNQ eG JjSQ ef gPG GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
(3GdfSNI HgG JdhjK s
Keywords: (3GdeLGejYs